88 Prospective Association of Obesity and Falls among Malaysian Community-Dwelling Older Adults. (20th December 2019) - Kioh, Sheng Hui; Mat, Sumaiyah; Myint, Phyo; Kamaruzzaman, Shahrul B; Tan, Maw Pin
Abstract: Background: Cross-sectional studies linking the association between obesity and falls are limited and their results are somewhat conflicting. The inconsistent evidence between obesity and falls could be explained by the utilization of different measures of obesity including BMI, WC, waist hip ratio (WHR) and percentage body fat (%BF) in different studies. Aims: To examine the prospective association between various measures of obesity and falls among community-dwelling older adults. Methods: We utilized data from the wave 1 and wave 2 of the Malaysian Elder's Longitudinal Research Study (MELoR). Basic demographic characteristics, medical history, lifestyle factors and falls history in preceding 12 months was recorded by computer assisted questionnaire in participant's home while anthropometric measurements, body composition assessments and physical performance were collected at the hospital during a hospital check-up at baseline. The main exposure variables were increased body mass index (BMI), waist circumference (WC), waist hip ratio (WHR) and percentage body fat (%BF) and the main outcome was self-report falls in the preceding 12 months at time of follow-up. Results: Among 746 participants at baseline and follow-up (mean age 68.9 ± 7.3 years, old, 56.7% women), 150(20.1%) individuals had ≥1 time of fall at follow-up. No differences in mean age and proportion of men and women among fallers and non-fallers. However, fallers were found to have higher WHR, lower percentage muscle mass and performed poorer in physical performance (p-value<0.01). Of the four obesity indicators, higher WHR at baseline was associated with increased risk of fall 12 months later even after adjustment for all potential confounders (aOR= 2.01; 95%CI= 1.26-3.18). Conclusions: In conclusion, our findings suggest that WHR is the measure of adiposity most likely to differentiate fallers from non-fallers prospectively. Future studies should evaluate the mechanisms underlying the increased risk of falls associated with increased WHR.